Combination of metformin and myoinositol: a powerful weapon to combat polycystic ovary syndrome - Sharma, Pragati; Malvi, Abhijeet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Polycystic ovary syndrome (PCOS) affects up to 13% of women of reproductive age, causing symptoms like menstrual irregularities, insulin resistance, and infertility. Insulin resistance is the root cause of PCOS. Metformin, an insulin-sensitizing drug, and Myo-inositol, a natural compound that enhances ovarian function and also an insulin sensitising agent, have both shown benefits in PCOS management. When combined, these agents act synergistically, that results in improved menstrual cycle regularity, reduction in hyperandrogenic symptoms, and enhancement in fertility outcomes. Recent clinical evidence supports this dual approach, and its approval for PCOS-related infertility treatment in India, along with endorsement by FOGSI, underscores its effectiveness as a promising therapeutic option for women with PCOS.